2013
DOI: 10.1080/02755947.2012.741555
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Habitat Differentiation among Adult Shoal Bass, Largemouth Bass, and Spotted Bass in the Upper Flint River, Georgia

Abstract: The Shoal Bass Micropterus cataractae is a fluvial specialist endemic to the Apalachicola River drainage in Alabama, Florida, and Georgia that has experienced declines throughout much of its range. The Flint River, Georgia, represents the largest remaining intact ecosystem for Shoal Bass in their native range. Spotted Bass M. punctulatus have recently been introduced into this system, causing concern about the potential negative impacts the species may have on the native populations of Shoal Bass and Largemout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 47 publications
4
41
0
Order By: Relevance
“…Similar percentages of immigrants in both the Ohio River and tributaries suggest that spotted bass movement between the river and tributaries was not unidirectional. Although there have been no prior investigations of spotted bass movement in large river systems, studies that have provided insights regarding the magnitude and frequency of spotted bass movement in small streams have indicated that movement tendencies are variable among streams and individuals within streams, likely dependent on habitat conditions (Funk, ; Goclowski et al., ; Horton & Guy, ; Lewis & Elder, ). Further studies are needed to elucidate factors influencing movement of spotted bass between mainstem rivers and tributaries and develop a greater predictive capacity regarding the extent to which tributary and mainstem environments support recruitment and may influence population dynamics of spotted bass in river–tributary networks.…”
Section: Discussionmentioning
confidence: 99%
“…Similar percentages of immigrants in both the Ohio River and tributaries suggest that spotted bass movement between the river and tributaries was not unidirectional. Although there have been no prior investigations of spotted bass movement in large river systems, studies that have provided insights regarding the magnitude and frequency of spotted bass movement in small streams have indicated that movement tendencies are variable among streams and individuals within streams, likely dependent on habitat conditions (Funk, ; Goclowski et al., ; Horton & Guy, ; Lewis & Elder, ). Further studies are needed to elucidate factors influencing movement of spotted bass between mainstem rivers and tributaries and develop a greater predictive capacity regarding the extent to which tributary and mainstem environments support recruitment and may influence population dynamics of spotted bass in river–tributary networks.…”
Section: Discussionmentioning
confidence: 99%
“…However, these inexpensive, lightweight (portable) sidescan sonar units can be deployed on almost any waterborne craft without the requirement of specialist knowledge of sonar and geodetics, and with little to no experience with acoustic remote sensing. This accessibility is behind the rapid increase in popularity of these sonar systems, among the scientific research community for benthic imaging in a range of aquatic environments, both marine and freshwater, lotic and lentic (Kaeser and Litts, 2008;Gonzalez-Socoloske et al, 2009;Collins et al, 2010;Kaeser and Litts, 2010;Havens et al, 2011;Goclowski et al, 2013;Kitchingman et al, 2013;Kaeser et al, 2013;Flowers and Hightower, 2013;Powers et al, 2014;Bilkovic et al, 2014;La Croix and Dashtgard, 2015;Sterrett et al, 2015;Froehlich and Kline, 2015;Buscombe et al, 2015;Cheek et al, 2016;Dunlop et al, 2016;Smit and Kaeser, 2016). Such spatially distributed benthic data are especially important in the development and evaluation of models for habitat suitability and vulnerability (e.g.…”
Section: The Democratization Of Sidescan Sonar Technologymentioning
confidence: 99%
“…This may have affected the frequency of tag returns, but a more likely interpretation is that these areas are important spawning areas that support aggregations of shoal bass during this season. At least one of these areas (Flat Shoals) contained dense schools of age-0 shoal bass in the summers of 2008 and 2009, which were the most abundant fish collected by backpack electrofishing in this area (Goclowski, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the species was considered to be relatively sedentary, usually found in close proximity to rocky habitat with significant current velocity (i.e., shoals) (Stormer & Maceina, 2009). Two telemetry studies on this species found that some fish moved up to 10 km to large shoal complexes during the spawning season, where they stayed for up to two months before returning to their tagging area (Goclowski et al, 2013;Sammons & Earley, 2015). If these migrations are common, then biologists must significantly increase the scope of management and conservation of this species.…”
Section: Introductionmentioning
confidence: 99%